Rising Food Price and Its Consequences - Regmi, Hem Raj (Journal of Agriculture and Environment, 2009)
Agricultural prices have risen worldwide sharply in the last two years, which has been a dilemma especially to policy makers. Higher agricultural prices would improve farmer's income and their living standards as well as investment in agriculture provided a fair mechanism of income transfer to them be instituted. However, the price rise seriously affects urban poors' food affordability and thus their livelihood. Various types of natural disasters particularly floods, droughts and landsides have affected agricultural crop production in Nepal resulting in fluctuations in food supplies and prices. Besides, policy measures associated with crop production, food balance and trade, petroleum price stabilization and liquor production directly or indirectly affect food market and prices. National food production, demand-supply, consumption and price scenarios and associated reasons are analyzed based on reviews of pertinent literatures. Key words: Food production, food consumption, demand-supply, price-scenario, Nepal The Journal of Agriculture and Environment Vol:.9, Jun.2008 Page: 93-97